Effect of ice stunning versus electronarcosis on stress response and flesh quality of rainbow trout - Bermejo-Poza, Ruben [UNESP]; Fernandez-Muela, Montserrat; De la Fuente, Jesus; Perez, Concepcion; Gonzalez de Chavarri, Elisabet; Teresa Diaz, Maria; Torrent, Fernando; Villarroel, Morris (Elsevier B.V., 2021)
In recent years, concerns about fish welfare have increased in aquaculture, most pointedly regarding the slaughter process. Immersion in ice water (live chilling) is still commonly used as a stunning method in salmonids, but can have negative effects on the stress response and flesh quality. A valid alternative is electronarcosis, but the specific details of the intensity and frequency of the current applied depend on the species and size, and little is known about how that may affect fish welfare or product quality. In this study, adult rainbow trout (294 ? 8.44 g average weight) were subjected to three different stunning methods before slaughter: immersion in ice water and electronarcosis at two different current intensities (200 or 400 mA). Electronarcosis caused fish to lose consciousness faster than those live chilled. Plasma concentration of cortisol was lower in fish stunned with 400 mA (400 mA: 5.2 ? 0.67 vs. Ice: 9.1 ? 0.90; 200 mA: 9.3 ? 1.20 ng/ml). Creatinephosphokinase enzyme levels were higher in ice stunned fish compared to electronarcosis (Ice: 168 ? 2.32 vs. 200 mA: 114 ? 0.89; 400 mA: 104 ? 0.62 U/l). Regarding flesh quality, initial muscle pH was lower in fish stunned by ice immersion than by electronarcosis (Ice: 6.49 ? 0.034 vs. 200 mA: 6.76 ? 0.050; 400 mA: 6.61 ? 0.04), presenting also an earlier onset of rigor mortis. Fish stunned with 400 mA electronarcosis also presented higher levels of muscle glycogen than those stunned with ice water (0.181 ? 0.029 vs. 0.101 ? 0.013 mg/g). In conclusion, electronarcosis is a stunning method that can produce an immediate loss of consciousness in rainbow trout, reducing stress response before slaughter and improving flesh quality (with higher benefits using a current intensity of 400 mA), in contrast to immersion in ice water.
Keywords: Stunning method; Pre-slaughter; Cortisol; Muscle pH; Rigor mortis